Unraveling the Potential Role of Probiotics in Ameliorating Hyperuricemia - Darmawan, Guntur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Hyperuricemia has gained clinical interest due to emerging evidence of its association with various diseases, such as hypertension, diabetes mellitus, cardiovascular disease, chronic kidney disease, and fatty liver. Gut dysbiosis has been suggested to be linked to hyperuricemia, as the gastrointestinal tract is responsible for approximately one-third of the total human uric acid excretion. Alterations in gut microbiota composition have been observed in individuals with hyperuricemia.. Probiotics have regained popularity due to their beneficial health effects, and several studies have shown their potential as a dietary intervention for hyperuricemia. This review aims to examine the intestinal dysbiosis in individuals with hyperuricemia and explore the role of probiotics in ameliorating uric acid levels.